2012
DOI: 10.1039/c1dt11379h
|View full text |Cite
|
Sign up to set email alerts
|

Photocrystallographic identification of metastable nitrito linkage isomers in a series of nickel(ii) complexes

Abstract: Single crystal photocrystallographic experiments and solid state Raman spectroscopy have been used to determine the low temperature, metastable structures of the nickel(ii) nitrito complexes [Ni(aep)(2)(η(1)-ONO)(2)] 1#O (aep = 1-(2-aminoethyl)piperidine), [Ni(aem)(2)(η(1)-ONO)(2)] 2#O (aem = 1-(2-aminoethyl)morpholine), and [Ni(aepy)(2)(η(1)-ONO)(2)] 3#O (aepy = 1-(2-aminoethyl)pyrrolidine and where the #O denotes the oxygen-bound nitrito metastable molecule). These linkage isomers of the equivalent nitro com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 65 publications
2
23
0
Order By: Relevance
“…In our efforts to gain a more complete understanding of the photochemical reaction in such systems we have investigated a number of transition metal complexes exhibiting solid-state nitro-nitrito linkage isomerism. As a result of studies aimed 70 at improving photoconversion levels we reported the first fully-reversible nitronitrito isomerism in the complex [Ni(dppe)(η 1 15 In addition we have reported the interesting behaviour of the tridentate amine complex [Ni(Et 4 dien)(η 1 -NO 2 ) 2 ], which undergoes reversible nitro-nitrito linkage isomerism following exposure to both UV light and heat, 16 and have also observed similar behaviour in the system [Pd(papaverine)(PPh 3 )(NO 2 )] on exposure to both of these stimuli. 17 These results indicate that the nature of the surrounding crystalline environment has an effect on the photochemical reaction, in-line with previous findings.…”
Section: Introductionmentioning
confidence: 99%
“…In our efforts to gain a more complete understanding of the photochemical reaction in such systems we have investigated a number of transition metal complexes exhibiting solid-state nitro-nitrito linkage isomerism. As a result of studies aimed 70 at improving photoconversion levels we reported the first fully-reversible nitronitrito isomerism in the complex [Ni(dppe)(η 1 15 In addition we have reported the interesting behaviour of the tridentate amine complex [Ni(Et 4 dien)(η 1 -NO 2 ) 2 ], which undergoes reversible nitro-nitrito linkage isomerism following exposure to both UV light and heat, 16 and have also observed similar behaviour in the system [Pd(papaverine)(PPh 3 )(NO 2 )] on exposure to both of these stimuli. 17 These results indicate that the nature of the surrounding crystalline environment has an effect on the photochemical reaction, in-line with previous findings.…”
Section: Introductionmentioning
confidence: 99%
“…We have direct experience of this approach as both a means to produce photoresponsive single crystals to examine the photoreactivity of particular chromophores in a framework environment, and to make materials with which to develop and demonstrate the emerging field of X-ray photocrystallography. [77][78][79][80][81][82][83][84][85][86][87][88][89] In 2009 we reported a combined spectroscopic and crystallographic study on the [Mn(DMF)2[LM(CO)3Cl]]∞ L = , -bipyridine-5,5-dicarboxylate; M = Re (ReMn) or M = Mn (MnMn)) which contains an (M(diimine)(CO)3Cl) unit as the linker, with the CO groups facially coordinated, combined with Mn nodes to form the 3D structure. 82 Ultrafast time-resolved FTIR and spatially resolved Raman mapping were used to characterise the short-lived excited states (picosecondnanosecond) of the parent facisomer and to determine the conditions required for photoinduced fac-mer isomerisation to occur.…”
Section: Iii) Framework With Photoresponsive Pendant Groupsmentioning
confidence: 99%
“…The conversion rate varied from 16% for endo-Ni(aep)(ONO) 2 after exposure to 470 nm light, to 46% for endo-Pd(PPh 3 ) 2 (ONO) 2 after exposure to 362 nm light (up from 30% using 400 nm light). In addition to displaying lower nitrite to nitrito conversion, the nitrito anions in Ni(aepy)(ONO) 2 Partial conversions could be obtained by illumination of Ni(aep)(NO2)2, Ni(aepy)(NO2)2 (aep = 1-(2-aminoethyl)piperidine, aepy = 1-(2-aminoethyl)pyrrolidine) [55], Pd(PPh3)2(NO2)2 and Pd(AsPh3)2(NO2)2 [56] (Figure 6). The conversion rate varied from 16% for endo-Ni(aep)(ONO)2 after exposure to 470 nm light, to 46% for endo-Pd(PPh3)2(ONO)2 after exposure to 362 nm light (up from 30% using 400 nm light).…”
Section: Photocrystallographymentioning
confidence: 99%
“…Partial conversions could be obtained by illumination of Ni(aep)(NO 2 ) 2 , Ni(aepy)(NO 2 ) 2 (aep = 1-(2-aminoethyl)piperidine, aepy = 1-(2-aminoethyl)pyrrolidine) [55], Pd(PPh 3 ) 2 (NO 2 ) 2 and Pd(AsPh 3 ) 2 (NO 2 ) 2 [56] (Figure 6). The conversion rate varied from 16% for endo-Ni(aep)(ONO) 2 after exposure to 470 nm light, to 46% for endo-Pd(PPh 3 ) 2 (ONO) 2 after exposure to 362 nm light (up from 30% using 400 nm light).…”
Section: Photocrystallographymentioning
confidence: 99%
See 1 more Smart Citation